Pharmacist's role in immune-related adverse events management: real-world incidence and risk evaluation from immunotherapy - Meanwatthana J. (2023)
Objectives: The challenge of using immune checkpoint inhibitors (ICI) is the immune-related adverse events (irAEs). Nonetheless, there is scarce evidence regarding the irAEs in Thailand. The primary aims of this study are to assess the incidence as well as risk factors of irAEs among cancer patients in Wattanosoth hospital. Methods: This was a cross-sectional retrospective chart review for the 3-year period (2017-2019). Data were collected after initiating the approved ICIs and patients were then followed for 12 months. The outcomes included incidences of irAEs, adverse events management, and tumor objective response. Bivariate analysis was performed for factors that might be associated with irAEs occurrences. Results: Data from 91 patients was collected. There was a 49.5% overall irAEs incidence. The most frequent irAE to occur affected the endocrine system (29.85%). In addition, we identified that odds ratios of irAEs development increased in patients who had four or more ICI cycles or had a serum creatinine level higher than 1.2 mg/dl, (OR: 1.75; 95% CI 1.1611:2.6256, P = 0.0074) and (OR: 1.58; 95% CI: 1.0628:2.3574; P = 0.0238), respectively. The emergence of irAEs may be a sign of tumor objective responses (OR: 1.79; 95% CI 1.0035:3.1889; P = 0.0486). Conclusion: This study demonstrates that irAEs are common in patients treated with ICIs. In addition, our study identifies that number of cycles and serum creatinine influence the development of irAEs. Hence, prompt recognition and an adequate monitoring plan should be cautiously taken into consideration.